PENGARUH PRODUKSI KONTEN KEBERAGAMAN DI SMK BAKTI KARYA PARIGI TERHADAP PENDIDIKAN MULTIKULTURAL - Aziz, Nur; Risma, Risma; Sri Handayani, Elin (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
Information technology is already present today, and SMK Bakti Karya Parigi is harnessing these tools to produce positive content, particularly focusing on diversity. This is supported by SMK Bakti Karya Parigi's multicultural class program. The purpose of this research is to examine the sources of influence of diversity content production at SMK Bakti Karya Parigi on multicultural education. The research method employed is qualitative descriptive with an observational (mini research) approach, conducted over a period of one week. This mini-research focuses on the impact of diversity content production at SMK Bakti Karya Parigi on multicultural education. Through observations at SMK Bakti Karya Parigi, the researchers discovered several indications that content produced on the topic of diversity has a significant influence on the audience, and they appreciate it, as evident in the interactions in the comment section. However, some challenges arise, specifically in terms of human resources, where the workforce comprises students who are learning to implement knowledge in broadcasting and filmmaking by creating diverse content published through the Metrum TV YouTube channel